Gambaran histologik hati pada kelinci yang diinduksi lemak dengan pemberian ekstrak beras hitam - Somba, Yosua R.; Wongkar, Djon; Ticoalu, Shane H. R.; Bolang, Alexander S. L. (Universitas Sam Ratulangi, 2016)
Abstract: Dyslipidemia is a disorder of fat metabolism which is marked by increase of one or more fractions of fat in the blood. Due to the high rate of dyslipidemia cases, people begin to improve their lifestyle, such as consuming black rice. Black rice (Oryza sativa L.) is a local variety of rice that contains pigments which are different from other types of rice. Black rice extract is beneficial for lowering LDL cholesterol level and significantly increasing HDL cholesterol level besides its antioxidant effect against reactive oxygen species. This was an experimental posttest-only control group design. Subjects were three New Zealand White rabbits, divided into three groups. Group A was fed with standard food for rabbit; group B was fed with standard food for rabbit and fat; group C was fed with standard foot for rabbit, fat, and black rice extract for 28 days. Blood total and LDL cholesterol were examined on the first day and after 28 days of treatment. The three groups were terminated and their liver tissues were processed for histological examination. The histological results were as follows: Group one showed small fat vacuoles around the hepatocyte nuclei; group two showed large fat vacuoles around the hepatocyte nuclei, signet rings, and coalescence of fat vacuoles; group three showed fat vacuoles around the hepatocyte nuclei, a few signet rings without coalescence of fat vacuoles. Conclusion: Black rice extract could reduce fat vacuoles in liver tissue.Keywords: fat, black rice extract, dyslipidemia, fatty liverAbstrak: Dislipidemia adalah kelainan metabolisme lemak yang ditandai peningkatan salah satu atau lebih dari fraksi lemak di dalam darah. Meningkatnya kasus dislipidemia menyebabkan banyak orang beralih ke gaya hidup sehat, antara lain mengonsumsi beras hitam. Beras hitam (Oryza sativa L.) merupakan beras varietas lokal dengan pigmen yang berbeda dari beras lain oleh karena kandungan antosianin. Ekstrak beras hitam bermanfaat untuk menurunkan kadar kolesterol total dan LDL secara bermakna, meningkatkan kadar kolesterol HDL, serta memiliki efek antioksidan terhadap reactive oxygen species. Jenis penelitian ini ialah experimental posttest-only control group design. Sampel penelitian ini ialah kelinci New Zealand White sebanyak 3 ekor yang dibagi menjadi 3 kelompok. Kelompok A diberi pakan standar; kelompok B diberi pakan standar dan lemak; dan kelompok C diberi pakan standar dengan lemak dan ekstrak beras hitam selama 28 hari. Pemeriksaan kkolesterol total dan LDL dilakukan pada awal penelitian dan 28 hari setelah perlakuan 28 hari. Kelinci diterminasi untuk pengambilan jaringan hati yang kemudian dibuat sediaan histologik. Hasil pemeriksaan histologik ialah sebagai berikut: Kelompok 1 menunjukkan adanya vakuola lemak kecil-kecil disekitar nukleus; kelompok 2 menunjukkan adanya vakuola lemak yang luas di sekitar nukleus, gambaran signet ring, dan penggabungan vakuola lemak; kelompok 3 menunjukkan adanya vakuola lemak disekitar nukleus dengan beberapa gambaran signet ring tanpa penggabungan vakuola lemak. Simpulan: Ekstrak beras hitam dapat mengurangi vakuola lemak pada jaringan hatiKata kunci: lemak, ekstrak beras hitam, dislipidemia, perlemakan hati